MANAJEMEN PEMBELAJARAN KITAB KUNING DALAM MEWUJUDKAN SEKOLAH UNGGUL - Makmum, Amir; Rizal Mz, Syamsul; Maulana, Irwan (JEDLISH : Journal Of Education and English Language Teaching, 2023)
The study of classic book which is carried out in schools has its own charm because the yellow book is a book that studies the products of previous scholars and is full of values ​​so it needs to be managed properly in order to give birth to a good education. This study aims to explain the phenomenon of learning the yellow book at Mafazah Middle School. This research method uses a qualitative approach using observation techniques, interviews, documentation studies, and data analysis techniques. This study found that learning planning was carried out to formulate goals, determine learning materials, learning strategies, and learning evaluation. Organizing is carried out by creating an organizational structure to carry out learning. Implementation of learning is done based on what has been planned. The evaluation is carried out based on daily evaluations and exams through reading the book